Histatin 5 metallopeptides and their potential against candida albicans pathogenicity and drug resistance - Zolin, Gabriela Vieira Silva [UNESP]; Fonseca, Fauller Henrique da [UNESP]; Zambom, Carolina Reis [UNESP]; Garrido, Saulo Santesso [UNESP] (MDPI, 2021)
Usually caused by Candida albicans, buccal candidiasis begins with the morphological transition between yeast and hyphal cells. Over time and without the correct treatment, it can be disseminated through the bloodstream becoming a systemic infection with high mortality rates. C. albicans already shows resistance against antifungals commonly used in treatments. Therefore, the search for new drugs capable of overcoming antifungal resistance is essential. Histatin 5 (Hst5) is an antimicrobial peptide of the Histatin family, that can be found naturally in human saliva. This peptide presents high antifungal activity against C. albicans. However, Hst5 action can be decreased for interaction with enzymes and metal ions present in the oral cavity. The current work aims to bring a brief review of relevant aspects of the pathogenesis and resistance mechanisms already reported for C. albicans. In addition, are also reported here the main immune responses of the human body and the most common antifungal drugs. Finally, the most important aspects regarding Histatin 5 and the benefits of its interaction with metals are highlighted. The intention of this review is to show the promising use of Hst5 metallopeptides in the development of effective drugs.
Keywords: Antifungal peptides; Candida albicans; Histatin 5; Metallopeptides